A Comparative study in character education management models in Indonesia and India - Yuliana, Lia; Sugiyono, Sugiyono; Mehta, Kunal (Harmoni Sosial: Jurnal Pendidikan IPS, 2021)
The purpose of this research is to find out: 1.) Character education management models in Indonesia and India: Comparative study at Universitas Negeri Yogyakarta and Lajpat Raj DAV College Jagraon India; and 2.) Effectiveness of Character education management models in Indonesia and India: Comparative Study at Universitas Negeri Yogyakarta and Lajpat Raj DAV College Jagraon India. The method of this research was qualitative research and used a comparative study design approach. This research’s most appropriate strategy was embedded research (stuck research) because the research has been planned in detail in the proposal before the researchers plunged into the field. The steps used were: 1.) Collecting source through multi-technique); 2) Reducing data to simplify and categorizing data; 3) Presenting data in the form of qualitative description; 4) Concluding; and 5.) Preparing research reports and formulating recommendations comparison research results. The research results show that the character education management model in Indonesia and India is almost the same. Whereas in Indonesia, it focuses more on religious and general characters, it is more on developing religious character in India. Meanwhile, the effectiveness of character education from Indonesia and India has been achieved by shaping students’ character and other components, both for lecturers and education staff. Meanwhile, in India, public awareness and educators of the importance of education.